Archéologie du bâti par méthode géoradar : le cas de la basilique Saint-Seurin de Bordeaux - Anne Michel; Jean-François Lataste (Bulletin du Centre d’Études Médiévales d’Auxerre)
The Saint-Seurin Church of Bordeaux is a structure continuously modified from the Middle Ages to the present day. It developed from a mausoleum of Late Antiquity, whose masonry was integrated into a crypt beneath the nave of the church. During an archaeological operation conducted there in 2015, Ground Penetrating Radar (GPR) investigations were carried out on the walls of the thick masonry of the chapels located in the crypt and on the floor of the church, in the nave and in the choir. They highlighted the structure of the masonry of the crypt, encompassing those of the Late Antiquity building, and strengthened the hypothesis of the existence of conduits extending from the chapels to the east of the crypt.